PP.42.15: ANGIOTENSIN II-DEPENDENT DIFFERENTIAL MIRNA EXPRESSION IN RAT RENAL EPITHELIAL TUBULAR CELLS. (June 2015) - Castoldi, G.; Giollo, F.; Di Gioia, C.; Carletti, R.; Antoniotti, M.; Perego, C.; Zerbini, G.; Stella, A.
Abstract : Objective: Angiotensin II (Ang II) plays an important role in renal disease progression, through complex mechanisms modulating gene expression/protein translation. MicroRNAs (miRs) are non-coding RNAs that control the expression of target genes. Renal epithelial tubular cells may acquire a profibrotic phenotype (epithelial-mesenchymal transition) in response to different stimuli. The aim of this study was to investigate miRNA differential expression in rat renal epithelial tubular (NRK-52E) cells in response to Ang II stimulation. Design and method: NRK-52E cells (90% confluence) were either stimulated with Ang II (0.5 μM, added to serum free medium every 24 hours) or maintained in serum free conditions for 72 hours. After miRNA extraction (Mirvana kit), miRNA microarray analysis was performed using the TaqMan® MicroRNA Low Density Array (Life Technologies). Targetscan and Miranda softwares were used to identify the gene targets of miRNAs that, after Ang II treatment, resulted to be differentially expressed. Alpha-smooth muscle actin (a-SMA) and e-cadherin expressions were evaluated by immunofluorescence and western blotting. Results: Ang II treatment caused a significant down-regulation of six miRNAs (miR-9, miR-200c, miR-125b*, miR-375, miR-425*, miR-532–5p) and an up-regulation of three miRNAs (miR-135a*, miR-690, miR-764–5p) in NRK-52E cells. Ang II also caused an increase in a-SMA and a decrease in e-cadherin expression, indicating a shift of tubular epithelial cells toward the mesenchimal phenotype. Gene ontology analysis of the putative target genes of Ang II-dependent differential expressed miRNAs has identified genes related to MAP-kinase pathway, solute carrier proteins and extracellular matrix proteins. Conclusions: These data demonstrate that Ang II modulates miRNA expression in NRK-52E cells, suggesting that Ang II could play a role in the pahogenesis and progression of renal diseases through the modulation of miRNAs.